Ultrafiltration-based drinking water service for SDG 6 in Pulau Kemarau - Herlina, Herlina; Nasir, Subriyer; Agustina, Sri; Bayusari, Ike; Hermawati, Hermawati; Caroline, Caroline; Rahmawati, Rahmawati; Adipradana, Wirawan; Rendyansyah, Rendyansyah (Universitas Muhammadiyah Malang, 2026)
This community service activity aimed to deploy, and commission decentralized drinking-water service points for a river-dependent community on Kemarau Island, Palembang, supporting Sustainable Development Goal 6 by expanding access to treated water at low operating cost. A needs-based field procedure included a site survey, raw-water intake assessment, demand and electrical-load estimation, UF–solar pumping system design, component selection, and installation of a 300 Wp photovoltaic array (3×100 Wp), a 100 Ah battery, a controller/inverter unit, a 450 W pump, an ultrafiltration (UF) unit, and 250 L/600 L storage tanks. The system then underwent commissioning tests (leak checks, pump start–stop tests, and continuous-run trials), operator training, and formal handover to the neighbourhood association. Results showed stable operation of the intake pump–UF pump–storage tank series. The 250 L treated-water tank filled within 20–30 minutes, indicating an effective flow rate of 8.3–12.5 L/min (≈500–750 L/h). Water appeared clearer and odourless, and pH increased from 5.5 (raw water) to 6.9 (treated water). The system demonstrated service readiness and initial treatment performance and may reduce reliance on grid/diesel pumping; however, routine logs and scheduled laboratory testing for turbidity and microbiological indicators are required to verify long-term water safety.